2011
DOI: 10.3791/2597
|View full text |Cite
|
Sign up to set email alerts
|

Modified Annexin V/Propidium Iodide Apoptosis Assay For Accurate Assessment of Cell Death

Abstract: Studies of cellular apoptosis have been significantly impacted since the introduction of flow cytometry-based methods. Propidium iodide (PI) is widely used in conjunction with Annexin V to determine if cells are viable, apoptotic, or necrotic through differences in plasma membrane integrity and permeability 1,2 . The Annexin V/ PI protocol is a commonly used approach for studying apoptotic cells 3 . PI is used more often than other nuclear stains because it is economical, stable and a good indicator of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
281
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(293 citation statements)
references
References 11 publications
4
281
0
2
Order By: Relevance
“…By following the manufacturer's instruction, we stained cells with FITC-annexin V and propidium iodide. Data were acquired and analyzed using Cell Quest Pro Software in FACSCalibur (Becton, Dickinson, San Diego, CA, USA) (27).…”
Section: Methodsmentioning
confidence: 99%
“…By following the manufacturer's instruction, we stained cells with FITC-annexin V and propidium iodide. Data were acquired and analyzed using Cell Quest Pro Software in FACSCalibur (Becton, Dickinson, San Diego, CA, USA) (27).…”
Section: Methodsmentioning
confidence: 99%
“…As it is known, PI has the ability to enter a cell when it loses the permeability of the membrane, indicating late apoptosis or necrosis, therefore, PI does not stain live or early apoptotic cells due to the presence of an intact plasma membrane (Rieger et al, 2011). In this respect, the results indicated that the chloroformic fractions from petroleum ether extract of inflorescences, and chloroformic fraction from ethanolic extract of leaves induced early pro-apoptotic response on A549 cancer cell lines (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Propidium iodide (PI) was used in conjunction with Annexin V to determine if the cells were viable, apoptotic, or necrotic from differences in the plasma membrane integrity and permeability. This approach is a universal and accurate method for detecting cell apoptosis [16]. As shown in (Fig 4A&4C), few apoptotic cells were detected in the untreated control.…”
Section: Resultsmentioning
confidence: 83%